2012
DOI: 10.1111/j.1708-8208.2011.00435.x
|View full text |Cite
|
Sign up to set email alerts
|

Conventional Multi‐Slice Computed Tomography (CT) and Cone‐Beam CT (CBCT) for Computer‐Aided Implant Placement. Part II: Reliability of Mucosa‐Supported Stereolithographic Guides

Abstract: Implant placement via CT- or CBCT-derived mucosa-supported SLA guides yielded similar deviation values. Results should be confirmed on alternative CBCT scanners.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
44
2
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 25 publications
0
44
2
2
Order By: Relevance
“…To the best knowledge of the authors, no studies were performed on the accuracy of virtually planned implant placement in the fully edentulous maxilla after an augmentation procedure. Also, in contrast to many other accuracy studies without augmentation procedure, the result of this study was interpreted in a clinically relevant manner by decomposing three‐dimensional results into the BL and MD directions.…”
Section: Discussionmentioning
confidence: 99%
“…To the best knowledge of the authors, no studies were performed on the accuracy of virtually planned implant placement in the fully edentulous maxilla after an augmentation procedure. Also, in contrast to many other accuracy studies without augmentation procedure, the result of this study was interpreted in a clinically relevant manner by decomposing three‐dimensional results into the BL and MD directions.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, deviations between planned and postoperative implant position, implant deviations were determined in a clinically relevant manner, that is, decomposed in a BL and MD vector, and not solely in a three‐dimensional distance as performed in most other studies …”
Section: Discussionmentioning
confidence: 99%
“…Several studies showed in vivo results on the accuracy of implant placement using surgical templates. However, most of these studies presented accuracy results consisting of a combination of fully edentulous and partially edentulous, different types of support of the surgical template and implant placement in both mandible and maxilla …”
Section: Discussionmentioning
confidence: 99%
“…Due to the lack of sufficient studies suitable for the representation of a valid sample, mean linear deviation values in the shoulder of the implants reported in previous similar studies (Arisan, Karabuda, Piskin, & Ozdemir, ; Casap, Wexler, Persky, Schneider, & Lustmann, ; Vercruyssen et al, ) were referenced, and commercial software (GPower, Dusseldorf, Germany) was used for the estimation of the required sample. As a requirement of the ethical committee, the calculation was performed on the implant level and a minimum n of 86.1 implants were calculated to detect 30% linear deviation difference between the shoulders of the test (dynamic navigation‐assisted implant surgery) and control groups (conventional freehand implant surgery) at α = 0.05 with 80% statistical power.…”
Section: Methodsmentioning
confidence: 99%
“…Centre points in the tip and the shoulder of the implants were marked and connected by a virtual line representing the axis. Deviations between the planned and placed implants (distance between the circle centre of the implant shoulder, tip and the angular deviation between axes of the implants) were calculated according to the previously established methodology (Arisan, Karabuda, & Ozdemir, ; Arisan, Karabuda, Piskin, et al, ), employing coordinates automatically provided by the software (Figure ). Measurement processes were undertaken by an individual (Dental assistant A. Atasoy) unaware of the patients and the techniques.…”
Section: Methodsmentioning
confidence: 99%